(untitled) (Revista Educação, Artes e Inclusão, 2025)
The Inclusion in Networks Program: special education policies, human training and the affirmation of diversity is an intermunicipal program, created based on research from the master’s course of the Graduate Program in Education, Contemporary Contexts and Popular Demands (PPGEduc) at the University Federal Rural do Rio de Janeiro (UFRRJ), which integrates the Special Education coordinations of municipal education networks in the Costa Verde/RJ Region that, in a collaborative way, seek to transform their cultures, policies and practices. One of the stages of the program was the execution of the 1st Forum of the Inclusion in Networks Program. The objective of the Forum was to facilitate and strengthen the articulation in a decentralized way and in networks with consequences in concrete actions for the consolidation of inclusion in education in the region of Costa Verde/RJ. Thus, in this article, in the light of Theodor Adorno’s studies, we sought to present and analyze the public policies related to the inclusion of people with disabilities in the region, as well as to reveal the organization and execution of the Forum, disclosing the possibilities and potential of the work collaboration between educational networks.